2006
DOI: 10.1021/jp054981j
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Single-Event Microkinetic Model for Alkane Hydroconversion in Different Aggregation States on Pt/H−USY-Zeolites

Abstract: A single-event microkinetic model for the catalytic hydroconversion of hydrocarbons on Pt/H-US-Y bifunctional zeolite catalysts developed for low-pressure vapor phase conditions was extended to cover high-pressure vapor phase and liquid phase conditions. The effect of the density of the bulk hydrocarbon phase on the physisorption as well as on the protonation steps of the reaction network was accounted for explicitly and can be interpreted in terms of "compression" of the hydrocarbon sorbate inside the zeolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(68 citation statements)
references
References 33 publications
1
67
0
Order By: Relevance
“…However, such an isotherm is empirical in nature and the estimated interaction parameters have no explicit physical meaning. In liquid-phase hydrocracking, a similar competitive physisorption step was modelled by quantifying the non-ideal behaviour of the physisorbed phase with excess parameters and the liquid fugacity coefficients of the individual components in the bulk phase [25]. The physical meaning of these excess parameters was clarified via a Born-Haber cycle and could be applicable at dense vapour phase conditions.…”
Section: Development Of a Physisorption Model Accounting For Micropormentioning
confidence: 99%
See 2 more Smart Citations
“…However, such an isotherm is empirical in nature and the estimated interaction parameters have no explicit physical meaning. In liquid-phase hydrocracking, a similar competitive physisorption step was modelled by quantifying the non-ideal behaviour of the physisorbed phase with excess parameters and the liquid fugacity coefficients of the individual components in the bulk phase [25]. The physical meaning of these excess parameters was clarified via a Born-Haber cycle and could be applicable at dense vapour phase conditions.…”
Section: Development Of a Physisorption Model Accounting For Micropormentioning
confidence: 99%
“…However, solvation effects which typically occur at dense phases and, consequently, at saturation conditions, might be responsible for these enhanced protonation enthalpies. These effects are denoted as 'protonation excess' and were quantified on a similar value of about -7.8 kJ mol -1 for a USY (CBV720, Si/Al = 15) zeolite during liquid-phase hydrocracking [25,26]. Considering the cracked product distribution, the advanced model is able to adequately reproduce the trends in the experimental data as the modelled yields of the 'cracking pairs', i.e., C 3 and C 13 , C 4 and C 12 , etc., exhibit a more pronounced formation of the lightest component, vide Figure 8 for the C 5 -C 11 pair.…”
Section: Advanced Model Accounting For Shape Selectivity and Size Entmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically the H 2 /HC pressure ratio was 13 to 375. The models were adapted to liquid phase conditions by considering that the density of the bulk reactant phase affects the physisorption as well as the protonation steps in the reaction network [25]. Under vapor phase reaction conditions, the paraffins react strictly in order of decreasing chain length because of competitive physisorption.…”
mentioning
confidence: 99%
“…Next to the change in physisorption competition, phase density has also an impact on the protonation. Carbocations are better stabilized at higher bulk phase density [25]. Denayer et al [27] reported that the rate of n-heptane conversion relative to n-nonane in a binary mixture was enhanced by more than a factor of 2 by changing the phase from vapor to liquid.…”
mentioning
confidence: 99%